2015
DOI: 10.1515/amsc-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multidimensional Data Visualization by Means of Self-Organizing Kohonen Maps to Evaluate Classification Possibilities of Various Coal Types / Zastosowanie Wizualizacji Wielowymiarowych Danych Za Pomocą Sieci Kohonena Do Oceny Możliwości Klasyfikacji Różnych Typów Węgla

Abstract: Multidimensional data visualization methods are a modern tool allowing to classify some analysed objects. In the case of grained materials e.g. coal, many characteristics have an influence on the material quality. The paper presents the possibility of applying visualization techniques for coal type identification and determination of significant differences between various types of coal. To achieve this purpose, the method of Kohonen maps was applied by means of which three types of coal -31, 34.2 and 35 (acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…The methods of forming these classes were analysed and it was found that they do not always form substantially coherent classes. Therefore, to determine the methods in particular classes, because of the excellent classification abilities, artificial neural networks -Kohonen networks were used (Jamroz, Niedoba 2015).…”
Section: Results Of the Classification Of Methodsmentioning
confidence: 99%
“…The methods of forming these classes were analysed and it was found that they do not always form substantially coherent classes. Therefore, to determine the methods in particular classes, because of the excellent classification abilities, artificial neural networks -Kohonen networks were used (Jamroz, Niedoba 2015).…”
Section: Results Of the Classification Of Methodsmentioning
confidence: 99%
“…The most reliable and well tested in the practice of designing and researching series and individual asynchronous engines. For example, the analysis [10] is carried out using the EHD method, this also applies to [11]. Let's note that the proposed EHD is composed with very substantial assumptions:…”
Section: Investigation Of the Moving Mode Of Heat Exchange Of Engine mentioning
confidence: 99%
“…Neural networks were often used for classification problems [53][54][55][56][57][58]. Statistical data analysis was also described [59].…”
Section: Bayes Classifiermentioning
confidence: 99%